Effect of taxonomic diversification of microalgae harvested from eutrophicated reservoirs on the chemical composition of biomass and effectiveness of methane fermentation. Issue 3 (16th September 2014) - Dębowski, M.; Zieliński, M.; Kupczyk, K.; Rokicka, M.; Hajduk, A.
<x xml:space="preserve">Abstract</x> The objective of this study was to determine the possibility of using microalgae biomass from natural water bodies as a substrate for methane fermentation and to verify the effect of taxonomic structure and other physicochemical traits of the biomass on the technological effectiveness of the process. Harvested algae was characterized by a diversified taxonomic structure and on the content of nitrogen compounds and concentration of organic compounds in biomass, that was subject to seasonal dynamics of changes. The highest technological effects of the methane fermentation process were achieved with microalgae biomass harvested in July. In this period, the predominating taxonomic group were the Cyanoprokaryota, with a significant contribution of Chlorophyta. The mean yield of biogas production reached 441.15 ± 19.03 cm3/g o.d.m., at the mean production rate of r = 98.99 cm3/day and a reaction constant of k = 0.224 1/day. The mean content of methane in biogas accounted for 68.68 ± 1.67%. The lowest technological effects linked with biogas production were determined in November. These were the periods of the vegetative season with Bacillariophyceae constituting the predominating taxonomic group. The total production of biogas accounted for 333.65 ± 18.85 cm3/g o.d.m. The methane content were at mean levels of 54.19 ± 2.31%. © 2014 American Institute of Chemical Engineers Environ Prog, 34: 858–865, 2015